Low Back Pain Ambulatory Medicine Cases - Arielle Berger; Parag Sheth; Sara Bradley (Association of American Medical Colleges, 2013)
Abstract This case-based exercise contains three vignettes designed to facilitate discussion of evaluation, diagnosis, and treatment of the most common causes of low back pain (LBP). After completing this exercise, learners will be able to list a broad differential diagnosis for LBP, prioritize a diagnosis based upon history and physical exam findings, and will be able to suggest appropriate work up and treatment. It also reviews key concepts in clinical medicine such as sensitivity and specificity of both diagnostic tests and physical exam signs and Choosing Wisely. The exercise is geared toward clinical medical students during their ambulatory, internal medicine or family medicine rotations. It can also be used for postgraduate internal medicine and family medicine trainees. The exercise takes one hour to complete in a small-group setting. This exercise offers an interactive method to gain knowledge and understanding of a complex but common clinical scenario. The didactic session has been well received by student learners and geriatric fellows serving as facilitators.